PENGARUH PENGALAMAN, INDEPENDENSI, SKEPTISISME PROFESIONAL AUDITOR, PENERAPAN ETIKA, DAN BEBAN KERJA TERHADAP KEMAMPUAN AUDITOR DALAM MENDETEKSI KECURANGAN - Dewi Larasati; Windhy Puspitasari (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2019)
This study to examine the inflluence of experience, independence, auditor professional scepticism, application of ethics, and workload on the ability of auditors in detecting fraud in the public accounting firm in Jabodetabek using multiple regression analysis. In this study using of hypothesis testing. The technique of sampling with convenience sampling approach. The study sample of 97 respondents in 14 public accounting firm in Jabodetabek. The result conclude that experience, independence, and workload have no effects on the ability of auditors in detecting fraud. While auditors professional skepticism and application of ethics have significant positive effects on the ability of auditors in detecting fraud.